2011
DOI: 10.1128/mcb.01187-10
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Toxic Oligomers by HspB1 as a Cytoprotective Mechanism

Abstract: Small heat shock proteins (sHsps) are molecular chaperones that protect cells from cytotoxic effects of protein misfolding and aggregation. HspB1, an sHsp commonly associated with senile plaques in Alzheimer's disease (AD), prevents the toxic effects of A␤ aggregates in vitro. However, the mechanism of this chaperone activity is poorly understood. Here, we observed that in two distinct transgenic mouse models of AD, mouse HspB1 (Hsp25) localized to the penumbral areas of plaques. We have demonstrated that subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 76 publications
7
71
1
Order By: Relevance
“…7C). Previous studies have shown that extracellular sequestration of A␤ oligomers, which are considered to be the principal toxic forms of A␤ (29 -31), into larger aggregates decreases neurotoxicity (44,45). Altogether, these data suggest that C1q prevents A␤ neurotoxicity by modulating neuronal gene expression to induce a neuroprotective response that requires LRP1B and GPR6 and that LRP1B, but not GPR6, may also prevent A␤ association with neurons (Fig.…”
Section: C1q Protects Immature and Mature Neurons Against Fibrillar Andmentioning
confidence: 56%
“…7C). Previous studies have shown that extracellular sequestration of A␤ oligomers, which are considered to be the principal toxic forms of A␤ (29 -31), into larger aggregates decreases neurotoxicity (44,45). Altogether, these data suggest that C1q prevents A␤ neurotoxicity by modulating neuronal gene expression to induce a neuroprotective response that requires LRP1B and GPR6 and that LRP1B, but not GPR6, may also prevent A␤ association with neurons (Fig.…”
Section: C1q Protects Immature and Mature Neurons Against Fibrillar Andmentioning
confidence: 56%
“…Recently, it has been demonstrated that, even when present at very low concentrations, molecular chaperones may inhibit the cytotoxicity of preformed misfolded oligomers formed by A, IAPP and HypF-N and fibrils formed by apolipoprotein C-II, by binding to them and converting them into larger aggregates (Ojha et al, 2011;Mannini et al, 2012, Binger et al, 2013. Interestingly, this chaperone-induced effect has been found to occur in the absence of any major structural reorganisation within the individual oligomers, which appear to maintain their overall structure and just assemble into larger species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the concomitant inhibition of oligomer toxicity and increased oligomer size induced by chaperones, via recruitment of more misfolded protein oligomers into the aggregates, has been interpreted to mean that chaperoneinduced clustering of oligomers is a strategy used by chaperones to inhibit oligomer toxicity (Ojha et al, 2011;Mannini et al, 2012, Binger et al, 2013Cascella et al, 2013a). By contrast, using single-molecule fluorescence techniques, it has been shown that clusterin and Bc are able to bind preformed oligomers of A and sequester them from dissociation or further growth into fibrils, revealing another possible mechanism of action of molecular chaperones which is binding in the absence of aggregate clustering (Narayan et al, 2011;Narayan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial peptidases PreP and IDE are capable of degrading Aβ in the mitochondrial matrix (6). Reproduced with permission, from Muirhead et al, 2010, Biochemical Journal, 426(3), [255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270]. © The Biochemical Society [14].…”
Section: Amyloid-binding Alcohol Dehydrogenase (Abad)mentioning
confidence: 99%